2007
DOI: 10.1021/jp072036k
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Macroscopic Properties of Protic Ionic Liquids by Ab Initio Calculations

Abstract: We have systematically investigated combinations of anions and cations in a number of protic ionic liquids based on alkylamines and used ab initio methods to gain insight into the parameters determining their liquid range and their conductivity. A simple, almost linear, relation of the experimentally determined melting temperature with the calculated volume of the anion forming the ionic liquid is found, whereas the dependence of the melting temperature with increasing cation volume goes through a minimum for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
56
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 43 publications
0
56
0
3
Order By: Relevance
“…For such studies substituted imidazolium, pyrrolidinium, pyridinium, and ammonium cations have been used along with fluorometalate, triflate, and bis(trifluoromethylsulfonyl)imide anions. Unfortunately, Krossings results do not correlate with experimentally obtained melting points for protic ionic liquids (PILs) reported by Markusson et al [23] The reason for the large deviations of the predicted from the experimental melting points is probably related to the general trend of increasing T m with the increasing size of the anions.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…For such studies substituted imidazolium, pyrrolidinium, pyridinium, and ammonium cations have been used along with fluorometalate, triflate, and bis(trifluoromethylsulfonyl)imide anions. Unfortunately, Krossings results do not correlate with experimentally obtained melting points for protic ionic liquids (PILs) reported by Markusson et al [23] The reason for the large deviations of the predicted from the experimental melting points is probably related to the general trend of increasing T m with the increasing size of the anions.…”
mentioning
confidence: 69%
“…In earlier work Krossing et al and Markusson et al showed that the calculated volumes are in good agreement with those obtained from crystal structure or density measurements. [22,23] As shown in Figure 1 there is no linear trend for T m as a function of volume. The highest melting points are found for the species I and VIII, in which neither cation, imidazolium and 1,2,3,4,5-pentamethylimidazolium, have specific interaction sites.…”
mentioning
confidence: 93%
“…[13] A simple model for estimating the melting points of ILs suggests that most likely the liquid behavior of ILs can be attributed to large, unsymmetrical ions with high conformational flexibility. [14,18,15] Recent studies reveal complex structures having microheterogenous polar and nonpolar domains [16,17] for imidazolium-based systems with extended side chains; this phenomenon is not observed when the side chains are shorter.…”
mentioning
confidence: 99%
“…In früheren Arbeiten von Krossing et al und Markusson et al wurde gezeigt, dass die berechneten Volumina gut mit denen übereinstimmen, die aus Kristallstrukturen oder Dichtemessungen gewonnen wurden. [22,23] Wie in Abbildung 1 gezeigt, erkennt man keinen linearen Trend für T m als Funktion des Volumens. Die höchsten Schmelzpunkte findet man für die Verbindungen I und VIII, in denen beide Kationen, Imidazolium und 1,2,3,4,5-Pentamethylimidazolium, keine spezifischen Wechselwirkungen beinhalten.…”
unclassified